Flora Fauna Biodiversity and CSR Implementation in the Mangrove Ecosystem of Bagan Serdang Village, North Sumatra Province. - Ahmad Muhtadi; Rusdi Leidonald; Kamto Triwibowo; Nurul Azmi (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightsMangrove sampling was conducted to use the "spot check" methodMangrove ecosystem of Bagan Serdang Village was categorized damaged Diversity of mangroves in the Bagan Serdang Village mangrove ecosystem was categorized moderate, but diversity of aquatic organisms was higher than the mangrove.Pertamina's CSR activities had an impact on environmental sustainability such as a habitat for various fauna and improving the community's economyAbstractInformation about mangrove and fauna biodiversity in Bagan Serdang Village is essential to be studied as a basis for assessing the management and utilization potential of mangrove. This information could be used as a reference in sustainable mangrove management. This study aims to determine the biodiversity of flora and fauna in the mangrove ecosystem of Bagan Serdang Village. The research location is divided into three areas, with three observation points. The study was conducted in August-September 2019. The sampling of mangroves was carried out using the Spot Check Method. The results showed that the types of mangroves found were 18 species from 12 families consisting of 14 species of true mangrove and four types of associated mangroves while the fauna found in the mangrove ecosystem of Bagan Serdang Village was 16 species of fish, nine species of crustaceans, 13 species of mollusks, four species of birds, one species of reptile, one species of mammal and one species of horse shoe crab. The results of the mangroves analysis in the Bagan Serdang Village's mangrove ecosystem, including in moderate heading to damage condition. This could be seen from the death of several trees and the flourishing of A. ilicifolius species as a marker of mangrove, which tends to be damaged. The diversity of mangroves in the Bagan Serdang Village is lower (1.63) compared to aquatic organisms that reach 2.09 - 2.44. Corporate responsibility or CSR that PT Pertamina (Persero) TBBM Medan Group carried out in the village of Bagan Serdang with mangrove planting activities and ecotourism, as well as the development of processed mangrove products, could increase the value of diversity and increase the economy of the surrounding community.